Minimum detectable activity concentration of online monitoring instrument in primary circuit of HTR-PM based on Monte Carlo simulation - Rui Nie; Yu Wang; Ziling Zhou; Feng Xie; Jun Zhao; Jianzhu Cao; Qian Ma; Xi Chen (Nuclear Engineering and Technology)
The failure fraction of tri-structural isotropic (TRISO)-coated particles in the fuel elements of the core is a key indicator for characterizing the radiation safety of a high-temperature gas-cooled reactor (HTGR) and can be determined from accurate measurement of the activity concentrations of noble gas fission products in the primary coolant. However, in the high-temperature gas-cooled reactor pebble-bed module (HTR-PM), the total γ activity concentration in the primary circuit is currently monitored online without individual nuclide resolution. In this study, an online monitoring instrument based on a HPGe detector is proposed to obtain the activity concentration of individual nuclide in real time. Geant4 simulates detection efficiency, background energy spectrum, and minimum detectable activity concentration (MDAC) of the monitoring system, which are key parameters for evaluating the reliability and feasibility of the system for detecting noble gas fission products. In addition, a method for quickly calculating the MDAC using fitting formulas with low and high precisions is proposed, meeting the accuracy requirements for engineering applications. This study promotes application of online nuclide resolution technology in HTGR for fast assessment of fuel-element performance in the core. The proposed rapid MDAC evaluation method for detection systems can also be applied in nuclear emergency monitoring.